ATTACK OF TUNISIAN PHOSPHATE ORE BY A MIXTURE OF SULFURIC AND PHOSPHORIC ACID: Kinetics study by means of Differential Reaction Calorimetry - Zamouri, Olfa Lachkar; khemaies, brahim; Bennour, Faten; Khattech, Ismail (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Mixture of phosphoric and sulfuric acid solutions was used to investigate the dissolution kinetics of natural phosphate by DRC. The effect of solid/liquid ratio, concentration, particle size, stirring speed and temperature reaction is examined. It was found that the dissolution rate increased with stirring speed and particle size. However, increasing solid/liquid ratio, concentration and temperature decreased the dissolution rate. It was determined that the dissolution rate fits in the first order of the pseudo-homogeneous reaction model. Tow negatives values of apparent activation energies were found in the range of 25 to 60 °C. The experimental data were tested by graphical and statistical methods and it was found that the following models were best fitted for the experimental data and an empirical equation for the process was developed. -ln (1 – x) = [2,2 E-09((S/L)0.75C -0.461G0.447(SS) 0.471exp (2671/T)]t.  T≤ 40°C -ln (1 – x) = [2,2 E-09((S/L)0.75C -0.461G0.447(SS) 0.471exp (6959/T)]t. T > 45°C